The influence of financial development on total fertility rate in Indonesia - Afriska, Rosa; Nugroho, Ris Yuwono Yudo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This study investigated the impact of financial development on the total fertility rate in Indonesia, hypothesizing that financial development significantly influences fertility rates. The objective was to ascertain the effects of financial development on Indonesia's total fertility rate, utilizing annual time series data from 1980 to 2021 obtained from the official websites of Bank Indonesia, the Central Bureau of Statistics, and the World Bank. The analysis employed the Autoregressive Distributed Lag (ARDL) method to examine the influence of the money supply in circulation (M2), Gross Domestic Product, and household consumption on the total fertility rate, with these variables serving as proxies for financial development. The study utilized a comprehensive data analysis approach, including stationary tests, cointegration bound tests, ARDL Model analysis for long-term and short-term effects, and classical assumption tests. The findings revealed that the money supply (M2) has a negative and significant impact on the total fertility rate, the Gross Domestic Product also negatively and significantly affects the total fertility rate, while household consumption positively and significantly influences the total fertility rate. These results underscore the multifaceted relationship between financial development and fertility trends in Indonesia.